Determinants of the Morning-Evening Home Blood Pressure Difference in Treated Hypertensives: The HIBA-Home Study - Lucas S. Aparicio; Jessica Barochiner; Paula E. Cuffaro; José Alfie; Marcelo A. Rada; Margarita S. Morales; Carlos R. Galarza; Marcos J. Marín; Gabriel D. Waisman (International Journal of Hypertension)
Background. The morning home blood pressure (BP) rise is a significant asymptomatic target organ damage predictor in hypertensives. Our aim was to evaluate determinants of home-based morning-evening difference (MEdiff) in Argentine patients. Methods. Treated hypertensive patients aged ≥18 years participated in a cross-sectional study, after performing home morning and evening BP measurement. MEdiff was morning minus evening home average results. Variables identified as relevant predictors were entered into a multivariable linear regression analysis model. Results. Three hundred sixty-seven medicated hypertensives were included. Mean age was 66.2 (14.5), BMI 28.1 (4.5), total cholesterol 4.89 (1.0) mmol/L, 65.9% women, 11.7% smokers, and 10.6% diabetics. Mean MEdiff was 1.1 (12.5) mmHg systolic and 2.3 (6.1) mmHg diastolic, respectively. Mean self-recorded BP was 131.5 (14.1) mmHg systolic and 73.8 (7.6) mmHg diastolic, respectively. Mean morning and evening home BPs were 133.1 (16.5) versus 132 (15.7) systolic and 75.8 (8.4) versus 73.5 (8.2) diastolic, respectively. Significant beta-coefficient values were found in systolic MEdiff for age and smoking and in diastolic MEdiff for age, smoking, total cholesterol, and calcium-channel blockers. Conclusions. In a cohort of Argentine medicated patients, older age, smoking, total cholesterol, and use of calcium channel blockers were independent determinants of home-based MEdiff.